Hook-wire assisted localization of a completely endophytic renal mass during three-dimensional laparoscopic partial nephrectomy: Presentation of our technique. Issue 2 (May 2022) - Ferakis, Nikolaos; Paparidis, Spyridon; Papatheodorou, Athanasios; Symeonidis, Evangelos N; Katsimantas, Antonios
Introduction: Totally endophytic renal masses may be invisible during laparoscopic partial nephrectomy, posing challenge to surgeons regarding tumor's identification and resection. Case presentation: A 22-year-old male was incidentally diagnosed with a completely endophytic, cT1a renal mass. Percutaneous Computed Tomography-guided insertion of a hook-wire was performed prior to laparoscopic partial nephrectomy. The hook-wire anchored centrally into the tumor and its extra-renal part was easily identified intraoperatively, contributing to tumor's identification and surgical excision. Total operative time was 185 min, warm ischemia time was 21.5 min, tumor excision time was 10 min, and total renorraphy time was 31 min. No complications were encountered perioperatively. The patient was discharged on the fourth postoperative day. Histology revealed a pT1a, clear-cell renal cell carcinoma, with negative surgical margins. Conclusions: Our first experience indicates that hook-wire guided excision of a completely endophytic renal mass during laparoscopic partial nephrectomy is feasible, safe, and cost-effective.